Microstructural insights into the influence of stress amplitudes on the crack nucleation mechanism of Ti–2Al-2.5Zr alloy using quasi in-situ tests - Shengkun Wang; Mengqi Li; Zuoliang Ning; Gang Chen; Zheng Liu; Jun Wu; Wenchun Jiang (Journal of Materials Research and Technology)
The fatigue cracking mechanism of Ti–2Al-2.5Zr alloy was investigated under different stress amplitudes. The evolution of fatigue damage was analyzed using quasi in-situ tests. The dependence of transgranular and intergranular crack nucleation on microstructure features was discussed in detail. The mechanisms of slip-induced and twinning-detwinning (T-D) induced crack nucleation were elucidated, respectively. It was found that, at the stress amplitude of 442 MPa, the slip damage, in the form of intrusions/extrusions, dominated crack nucleation. Transgranular cracks primarily nucleate along the prismatic planes of the variants with highest Schmid Factor of prismatic slip (SFpris.); intergranular cracks are mainly induced at grain boundaries (GBs) by slip impacting/shearing GB behaviors and at GB triple junctions due to strain incompatibility. As the stress amplitude increased to 475 MPa, the dominant crack mode transitioned from slip-dominant cracks to T-D induced cracks and intergranular cracks due to the competition between the T-D and slip behavior. Twin boundaries (TBs), GBs, slip planes adjacent to the activated T-D regions, and the twin pairs/chains in adjacent grains were identified as preferred sites for crack nucleation.